Sealing properties of some root filling materials evaluated with radioisotope - Holland, Roberto; De Souza, Valdir; Abdalla, Tufy; Russo, Marty C. (Wiley, 1974)
Abstract— Penetration of a solution of 1131 was observed in vitro in the apical zone of root canals of human teeth filled with zinc oxide eugenol, Rickert's root sealer and Alpha canal paste. With thicker mixes generally less penetration using lateral condensation compared with the thick mix and single cone or fluid mix and lateral condensation. 1974 Australian Dental Association